Rewards modulate saccade latency but not exogenous spatial attention - Dunne, Stephen; Ellison, Amanda; Smith, Daniel T. (Frontiers in Psychology, 2015)
The eye movement system is sensitive to reward. However, whilst the eye movement system is extremely flexible, the extent to which changes to oculomotor behaviour induced by reward paradigms persist beyond the training period or transfer to other oculomotor tasks is unclear. To address these issues we examined the effects of presenting feedback that represented small monetary rewards to spatial locations on the latency of saccadic eye movements, the time-course of learning and extinction of the effects of rewarding saccades on exogenous spatial attention and oculomotor IOR. Reward feedback produced a relative facilitation of saccadic latency in a stimulus driven saccade task which persisted for 3 blocks of extinction trials. However this hemifield-specific effect failed to transfer to peripheral cueing tasks. We conclude that rewarding specific spatial locations is unlikely to induce long-term, systemic changes to the human oculomotor or attention systems.